EARLY DISCONTINUATION OF FONDAPARINUX IN LOW-RISK PATIENTS HOSPITALIZED WITH NON-ST-ELEVATION ACUTE CORONARY SYNDROME: MARKERS OF HEMOSTASIS ACTIVATION AND IN-HOSPITAL OUTCOMES - I. S. Yavelov; A. S. Knyazev; A. B. Dobrovolsky; N. A. Gratsiansky (Российский кардиологический журнал)
Current guidelines recommend use of anticoagulants (preferably fondaparinux) until hospital discharge in non-invasively treated patients (pts) with non-ST-segment elevation acute coronary syndrome (NSTEACS).  however, some evidence exists that anticoagulants may be safely stopped earlier in low-risk aspirin-treated pts. Aim. To assess markers of hemostasis activation and in-hospital events rate after very early discontinuation of fondaparinux in non-invasive treatment of low-risk pts hospitalized with NSTEACS. Material and methods. 53 pts admitted with NSTEACS at median 2,3 h after last episode of chest pain were included into prospective non-comparative study. All pts had GRACE score ≤108, negative tn t (cut-off 0,03 ng/ml), and no st-segment deviation >0,1 mV. Aspirin and beta-blockers were used in all cases while clopidogrel in 35 (66,0%) only. After single subcutaneous injection of fondaparinux at presentation no anticoagulants were used. Plasma thrombin-antithrombin (tAt), d-dimer (dd), plasmin-antiplasmin (PAP) levels, plasminogen activator inhibitor-1 (PAI-1) activity and its complex with tissue plasminogen activator (tPA/PAI-1) level were measured at median 18,0 and 42,5 hours after fondaparinux. 12-lead ECG monitoring was started at median 21,2 h after fondaparinux and continued for median 38,6 h.  Treadmill stress test was performed on days 4-18 (median 9) after hospitalization. Pts were followed until hospital discharge (median 14 days). Results. Plasma  tAt ,  dd and PAP levels increased after discontinuation of  fondaparinux: medians 3,1 and 3,3 ng/l (p=0,002), 359 and 486 ng/l (p=0,002), 471 and 498 ng/l (p=0,052), respectively. Increase at least one of these markers of hemostasis activation was revealed in 49 (92,5%) pts. Ischemic  st-segment deviations on ambulatory ECg were found in 13 pts (24,5%). First episode appeared at median 51,8 hours after fondaparinux and only one was symptomatic. tAt , dd and PAP levels as well as their changes were not associated with recurrence of ischemia. Positive result of treadmill test was obtained in 12 Conclusion. While in non-invasive treatment of low-risk nstEACs pts very early discontinuation of fondaparinux was associated with activation of coagulation this laboratory finding was not related to recurrence of ischemia and clinical events rate was low. (25,0%) pts (5 with and 7 without ischemic  st-segment deviations on ambulatory ECg; p=0,25).  during hospital stay, no patient died or had myocardial infarction; 3 had recurrent angina.